Student’s Community Service Involvement: Implications for a Sustainable Community Extension Service - John Mark R. Asio; Dante P. Sardina; Judy Ann O. Olaguir (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the student’s community service involvement at a local higher education institution in Olongapo City, Philippines. We used a descriptive-correlation design to 101 students who responded to the online survey during the second semester of the academic year 2021-2022. The result shows that students